(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
An accurate RP-HPLC method developed for the estimation of Neratinib in bulk and tablet dosage form. The method is and validated for parameters linearity, accuracy, suitability, specificity, precession, LOD, LOQ and robustness. An Altima column (150 mm × 4.6 mm × 5µ) used for chromatographic separation within a runtime of 6 min. The mobile phase buffer (monopotassium phosphate) and acetonitrile (60:40 v/v) with 0.1% formic acid is used. The flow rate maintained at 1.0 ml/min with the effluents monitored at 215 nm. The Neratinib analyzed at retention time of 4.001. The concentration linear over 30-180µg/ml with regression equation y = 6065.6x + 795.43 and regression co-efficient 0.999.